2005
DOI: 10.1002/cbic.200500057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ZnII Binding to the Peptide Amyloid‐β1–16 linked to Alzheimer's Disease

Abstract: Aggregation of the human peptide amyloid-beta (Abeta) is a key event in Alzheimer's disease (AD). Zinc ions play an important role in AD and in Abeta aggregation. In vitro, Zn(II) binds to Abeta and accelerates its aggregation. In this work we have investigated Zn(II) binding to the synthetic peptide Abeta1-16, which contains the metal-binding domain of Abeta. Cd(II) was used to probe the Zn(II) site. Abeta1-16 bound one equivalent of Zn(II) with an apparent dissociation constant (Kd) of 10(-4) M. This Kd valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
85
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 41 publications
19
85
0
1
Order By: Relevance
“…Finally, other results obtained by structural studies, have shown that this peptide has two metal binding sites with higher and lower affinity: copper in high affinity site is coordinated in a planar configuration with three histidines and terminus or Tyr10 and this binding site is able to bind also a zinc ion [21,22,25]. The four aminoacids proposed for zinc binding site are Tyr10, Glu11, Arg5 or the N-terminus [6,[26][27][28][29]. It has been made hypothesis about the presence for both metals in the second low affinity binding site but it is still studying [30][31][32].…”
Section: Introductionmentioning
confidence: 71%
“…Finally, other results obtained by structural studies, have shown that this peptide has two metal binding sites with higher and lower affinity: copper in high affinity site is coordinated in a planar configuration with three histidines and terminus or Tyr10 and this binding site is able to bind also a zinc ion [21,22,25]. The four aminoacids proposed for zinc binding site are Tyr10, Glu11, Arg5 or the N-terminus [6,[26][27][28][29]. It has been made hypothesis about the presence for both metals in the second low affinity binding site but it is still studying [30][31][32].…”
Section: Introductionmentioning
confidence: 71%
“…According to several studies, high concentrations of Al and Zn may be associated to the formation of b-amyloid in the brain, which are implicated in Alzheimer's disease (Bush et al 1994;Zatta et al 2002;Kaizer et al 2005;Mekmouche et al 2005); therefore it should not be excluded the hypothesis of these metals being mobilized from the lung, liver or kidney to the brain where they act as neurotoxicants. The levels of apoptotic nuclei, in all organs, were higher in mice from Furnas than in those from Rabo de Peixe.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation of the N-terminus does not inhibit zinc binding to the N-terminal fragment Ab(1-16), but the fourth ligand is proposed to be Glu11 in this variant [36]. In the same fragment but without an acetylated N-terminus, Asp1 was suggested to be the fourth ligand [35]. Recently Syme et al published a study on Ab(1-16) and Ab(1-28) in which they also suggested the fourth ligand to be the N-terminus, and indeed an N-terminal-blocked variant of Ab(1-28) showed less effects when zinc was added [45].…”
mentioning
confidence: 94%